2018
DOI: 10.2478/jwld-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Drought and water mobilization in semi-arid zone: The example of Hammam Boughrara dam (North-West of Algeria)

Abstract: The dam of Hammam Boughrara is an embankment dam built in a transboundary basin, between Algeria and Morocco; it was type-approved and delivered in 1998. This dam was supposed to solve the lack of drinking water in Oran (Algeria's second largest city) and enhance the agricultural perimeter of the area. It should regulate an annual water volume of 59 million m3. However, the northwest Algeria has experienced a fairly severe drought since the 80s. This article aims to show the impact of this drought on the amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(7 reference statements)
1
4
0
Order By: Relevance
“…Several studies have indicated the same results in line with our research [ADJIM, DJEDID 2018;HAMLAOUI-MOULAI et al 2013;HAMMAR et al 2014;KHEZAZNA et al 2017;MEDEJERAB, HENIA 2005], as these studies showed that the 1980s experienced a decrease in the rainfall, and considered as a dry sequence, it was observed mostly that drought index is often less than -1.…”
Section: Comparative Evaluation Of Drought Indicessupporting
confidence: 88%
See 1 more Smart Citation
“…Several studies have indicated the same results in line with our research [ADJIM, DJEDID 2018;HAMLAOUI-MOULAI et al 2013;HAMMAR et al 2014;KHEZAZNA et al 2017;MEDEJERAB, HENIA 2005], as these studies showed that the 1980s experienced a decrease in the rainfall, and considered as a dry sequence, it was observed mostly that drought index is often less than -1.…”
Section: Comparative Evaluation Of Drought Indicessupporting
confidence: 88%
“…(2) Determine the correlations between SPI and other indices (RAI, DI, PN), using the correlation coefficients of Pearson and Spearman. SPI is considered for analysing its correlation with other three indices because it is most often used as the measure in the drought analysis [GUTTMAN 1998;HAYES et al 1999], and most applied index to analyse meteorological drought in the northwest region of Algeria [ADJIM, DJEDID 2018;DJELLOULI et al 2016;. This proves the applicability of the comparison of SPI with the rest of the indices that have not yet received much attention in this part of the areas a primary step in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Log-normal and Weibull distributions were usually recommended and most frequently used for low flow evaluation, but there are no specific standards on which techniques to use for which data. The most commonly used and recommended log-normal and Weibull distributions [39,[81][82][83]. The Weibull distribution for low values occurs when the extreme value is from a parent distribution which is restricted in the interest direction which is in the event of low flows, they are bounded by zero flow on the left.…”
Section: Drought Severitymentioning
confidence: 99%
“…Further, SHIAU [2003] noted that reservoir is an important facility in multi-sector water supply system with the main function is to regulate the fluctuating surface water flow. Reservoirs have many benefits, such as flood control, recreational activities, hydroelectric and water supply, which may conflict each other [FRANCISCO et al 2016ADJIM, DJEDID 2018, water reservoir management must consider natural variability, especially climate change and land use change. Several studies have shown that climate change affects the performance of reservoirs due to the extreme reduction of reservoir capacity [BURN, SIMONOVIC 1996;FOWLER et al 2003;LI et al 2010;LOPEZ et al 2009;NAWAZ, ADELOYE 2006].…”
Section: El-ninomentioning
confidence: 99%